Internal Fault Detection, Location, and Classification in Stator Winding of the Synchronous Generators Based on the Terminal Voltage Waveform - M. Fayazi; F. Haghjoo (AUT Journal of Electrical Engineering)
In this paper, a novel method is presented for detection and classification of the faultyphase/region in the stator winding of synchronous generators on the basis of the resulting harmoniccomponents that appear in the terminal voltage waveforms. Analytical results obtained through DecisionTree (DT) show that the internal faults are not only detectable but also they can be classified andthe related region can be estimated. Therefore, this scheme can be used to protect the synchronousgenerators against the various internal faults. Fuji technical documents and data sheets for an actualsalient pole synchronous generator (one unit of an Iran’s hydroelectric power plants) are used for themodeling. Simulations in Maxwell software environment are presented. All the related parameters, suchas B-H curve, unsymmetrical air gap and pole saliency, slot-teeth effect, and other actual parameters, areconsidered to obtain a comprehensive model to generate acceptable terminal voltage waveforms withoutany simplification.